Blockchain enabled applications : understand the blockchain ecosystem and how to make it work for you - Dhillon, Vikram (Research fellow); Metcalf, David; Hooper, Max (CEO of Merging Traffic) (Apress, 2021)
Learn all about blockchain and its applications in cryptocurrency, healthcare, Internet of Things, finance, decentralized organizations, and more. Featuring case studies and practical insights, this book covers a unique mix of topics and offers insight into how to overcome hurdles that arise as the market and consumers grow accustomed to blockchain-based organizations and services. The book is divided into three major sections. The first section provides a historical background to blockchain technology. You will start with a historical context to financial capital markets when Bitcoin was invented, followed by mining protocols, the need for consensus, hardware mining, etc. Next, a formal introduction to blockchain is provided covering transaction workflow, role of decentralized network, and payment verification. Then, we dive deep into a different implementation of a blockchain: Ethereum. The main technical features, such as Ethereum Virtual Machine, are presented along with the smart contract programming language, Solidity. In this second section, you will look at some modern use cases for blockchain from a decentralized autonomous organization, high-performance computing in Ethereum and off-grid computations, and healthcare and scientific discovery. The final section of the book looks toward the future of blockchain. This is followed by chapters covering the rise of consortia in the blockchain world, the Hyperledger project, particularly the updates since 2018, and a chapter on educational blockchain games. This is followed by updates to EOS. IO, Chain Core, and Quorum, ICOs and a look at the major changes to financial markets brought about by blockchain and decentralized networks. You will: Get an overview of the popular games employed to teach the basic concepts of blockchain and decentralized networks Be familiar with the rise of blockchain consortiums as well as updates to Hyperledger Project, 2020 Find out about cloud blockchains, including Microsoft Azure and Amazon Webservices, and how to set up test environments Study machine learning integration in the blockchain and the role of smart contracts.